The impact of immune dysregulation on the risk of malignancy in common variable immunodeficiency: insights from a multicenter study - Cabañero-Navalon, Marta Dafne; Garcia-Bustos, Victor; Balastegui-Martin, Héctor; Bracke, Carmen; Mateu, Lourdes; Solanich, Xavier; Carrillo-Linares, Juan Luis; Robles-Marhuenda, Angel; Puchades, Francesc; Pelaez Ballesta, Ana; Lopez-Osle, Nuria; Torralba-Cabeza, Miguel Ángel; et al. (Frontiers in Immunology, 2024)
Background Common Variable Immunodeficiency (CVID) represents a heterogenic group of primary immunodeficiencies (PID) characterized by impaired antibody production and susceptibility to infections. Non-infectious complications, such as autoimmune diseases, lymphoproliferative disorders, and malignancies, now significantly impact prognosis. Moreover, both hematologic and solid organ malignancies are more frequently observed in CVID patients compared to other PIDs. The risk factors for carcinogenesis in CVID remain largely unknown. Objective This multicenter study aims to characterize the clinical profile of cancer in CVID patients in Spain and to identify independent risk factors associated with malignancy development, focusing on the role of immune dysregulation. Methods A nationwide, cross-sectional study was conducted from November 2019 to May 2022, involving 17 hospitals treating PID patients in Spain. Data were collected systematically on demographics, infectious and non-infectious comorbidities, immunological parameters, and treatment. Statistical analysis, including multivariate logistic regression, was performed to identify risk factors associated to malignancy. Results Of 250 CVID patients, 38 (15.26%) were diagnosed with cancer, predominantly non-Hodgkin lymphoma, gastric cancer, and lung adenocarcinoma. Cancer patients were significantly older (mean age 60.70 vs. 49.36 years, p<0.001) and had higher rates of immune dysregulation (81.58% vs. 59.7%, p=0.01). Immune dysregulation was an independent risk factor for cancer (OR 2.19, p=0.04), alongside previous immunosuppressant therapy (OR 2, p=0.031), higher IgM levels (OR 1.008 per SD, p=0.012), older age (OR 1.04, p<0.001), and lower CD4 cell counts at diagnosis (OR 0.997, p<0.001). Conclusions This study highlights the increased cancer risk in CVID patients, with immune dysregulation, prior immunosuppressant use, elevated IgM levels, and lower CD4 cell counts as conjointly associated. These findings underscore the need for vigilant cancer screening and tailored management strategies in CVID patients to improve outcomes. Future research should focus on elucidating the molecular mechanisms linking immune dysregulation and malignancy in CVID.